The health of youth: draft resolution proposed by the delegations of Bangladesh, Canada, Democratic People's Republic of Korea, Finland, France, Hungary, Iceland, Kenya, Lesotho, Mali, Malta, Nicaragua, Nigeria, Norway, Pakistan, Samoa, Sweden, Trinidad and Tobago, Turkey, United Kingdom of Great Britain and Northern Ireland and the United Republic of Tanzania - World Health Assembly, 42 (World Health Organization, 1989)
(Agenda item 18.2)